Pyrolysis of palm oil shell / Mastura Junus - Junus, Mastura (Faculty of Applied Sciences, 2009)
In this project, the use of technology such as pyrolyzer can recovery the product yield of biomass such as oil, char, and gas. In this research also, oil palm shell waste was pyrolyzed by using fast pyrolysis reactor the temperature 350°C, 400°C, 450°C and 500°C. This sample was used to characterized the raw and char sample produced by proximate and ultimate analysis. Maximum pyrolytic oil produced was found to be at 22.47 wt% at 400°C. The liquid was characterized by Gas Chromatography Mass Spectrometer was found to contain a very high concentration of phenol of total liquid oil. Factors that contribute in the distribution of pyrolytic oil produced in pyrolysis process were temperature of the pyrolysis reactor at 400°C, the solid residence time for four hours, 0.5mm particles size of biomass sample and the 8°C /min of gas flow rate utilized. This research only study about the effect of pyrolysis reactor playing an important role in distribution of product yield. The percentage of product yield was different in different temperature of pyrolysis reactor.